Curriculum Development Based on Digital Supply Chain Management in Learning Supplies Management Majoring in Office Administration - Adi Dharma, Buyung; Gunawan, Ari (Jurnal Sains dan Teknologi, 2023)
Planning, monitoring, and assessing an organization's inventory management processes—often referred to as supply and supply chains—involves learning about supply chains and infrastructure or supplies. We acknowledge, however, that supply management is currently rudimentary and falls short of the demands of Indonesia's expanding appointment market. This study's main goal is to raise the caliber of potential personnel who will handle supplies and equipment in a business. Design Thinking in advance was the methodology utilized in this study. It consists of five steps: empathy, definition and idealization, prototyping, product testing, evaluation, and preparation. This study's findings are integrated supply chain learning that is cloud-based. The introduction of various learning features including LMS, inventory, supply chain, and IoT tracking. There are also some instructions on how to practice bidding based on the case studies given due of the inventory feature. Students are given content for cognitive learning through LMS. Prospective employees' quality, particularly that of professional students studying organizational needs and materials management, can be raised by employing these tools. The creation and deployment of an integrated learning cloud related to subjects on a larger scale can be the focus of this research's continuation the following year